2014
DOI: 10.1371/journal.pone.0092337
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Tropical Analysis of Climate Effects on Seasonal Tree Growth

Abstract: Climate models predict a range of changes in tropical forest regions, including increased average temperatures, decreased total precipitation, reduced soil moisture and alterations in seasonal climate variations. These changes are directly related to the increase in anthropogenic greenhouse gas concentrations, primarily CO2. Assessing seasonal forest growth responses to climate is of utmost importance because woody tissues, produced by photosynthesis from atmospheric CO2, water and light, constitute the main c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
53
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 107 publications
13
53
2
6
Order By: Relevance
“…The main difference between the 3 scenarios lies in the absolute values of the Survivors' ACS loss, with very high values for the wet scenario. This result may look strange given that drought has often been identified as one of the main climate drivers of tropical forest dynamics Wagner et al 2012Wagner et al , 2013Wagner et al , 2014Wagner et al , 2016, with large mortality events among tropical trees during El Nino years for instance (Phillips et al 2009) that have not only immediate but also long-term and cumulative impacts on the carbon cycle (Doughty et al 2015). Those large mortality events are associated with tree hydraulic traits, the most susceptible species being those having a low hydraulic safety margin (Anderegg et al 2016).…”
Section: Exogeneous Driversmentioning
confidence: 99%
“…The main difference between the 3 scenarios lies in the absolute values of the Survivors' ACS loss, with very high values for the wet scenario. This result may look strange given that drought has often been identified as one of the main climate drivers of tropical forest dynamics Wagner et al 2012Wagner et al , 2013Wagner et al , 2014Wagner et al , 2016, with large mortality events among tropical trees during El Nino years for instance (Phillips et al 2009) that have not only immediate but also long-term and cumulative impacts on the carbon cycle (Doughty et al 2015). Those large mortality events are associated with tree hydraulic traits, the most susceptible species being those having a low hydraulic safety margin (Anderegg et al 2016).…”
Section: Exogeneous Driversmentioning
confidence: 99%
“…Moreover, the variability of the dry season length in Amazonia [6] has been underestimated in the climate models used for the IPCC 5th assessment report so that the projected changes of the dry-season length are likely to be the lower bound of the ongoing changes [7]. Recent studies have tried to understand the potential impact of this increase in water stress on tropical forests [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In tropical forests, high rainfall intensity in the rainy season is often associated with reduction in the levels of irradiance in response to cloudiness (Mulkey et al, 1996;Wagner et al, 2014). Therefore, it can be expected that an increase in irradiance leads to increase in tree growth (Graham et al, 2003;Stark et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that in central Amazonia carbon gains tend to be higher in the rainy season (Malhi et al, 1998;Vieira et al, 2004;Wagner et al, 2014). However, there is not conclusive evidence that soil water content is a limiting factor in the dry season, as somehow gross primary production starts to increase at the end of the dry season (Restrepo-Coupe et al, 2013), when soil water content is still at its lower levels (42% v/v, Malhi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%